Highly Stereoselective Asymmetric Total Synthesis of (−)-Jimenezin via Sequential Intramolecular Amide Enolate Alkylation - Lu, Thien Nhan; Kwak, Minjung; Samala, Mallesham; Son, Minji; Hwang, Jungjoong; Mandava, Suresh; Pham, Thuy Trang; Park, Haeil; Kim, Hyoungsu; Kim, Deukjoon; Lee, Jongkook (Organic Letters, 2022)
A highly stereoselective asymmetric total synthesis of (−)-jimenezin (1), a potent anticancer acetogenin, was efficiently completed with the key feature being a sequential intramolecular amide enolate alkylation (IAEA). Our investigation to probe the origin of the complete stereoselectivity in the second IAEA step to form the conformationally flexible tetrahydrofuran with perfect stereocontrol identified the presence of the oxygen atom in the adjacent tetrahydropyran ring to be crucial.